Sport: An Ethos Based on Values and Servant Leadership - DeSensi, Joy T. (Journal of Intercollegiate Sport, 2014)
Concluding remarks for this special issue of the Journal of Intercollegiate Sport on Ethical Leadership in Intercollegiate Sport note the numerous breaches of ethical and moral behavior in a physical and personal space that have the potential to develop character, moral development, self-efficacy, respect, and personal honorable significance. While it is easier to speak from higher ground, regarding ethical behavior in intercollegiate athletics, the implementation of such is a problem held by many of those associated with this level of sport. The challenges are many in this area and the actions are met with resistance when massification and commodification are considered regarding sport in the educational setting. The direction of this paper is to educate those who are or will be in roles affiliated with intercollegiate sport by developing an ethical awareness of their moral values and creating a legacy of action based on servant leadership.